COMMISIVE SPEECH ACT IN THE SECOND US PRESIDENTIAL DEBATE - SARI, NOVIKA NEGRITA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Speech Acts, Commisive Speect Acts Verbs, Direct Speech acts, Indirect Speech, Second US Presidential Debate.Communicating is one of the fundamental requirements for someone to be able to understand each other. In this study, the writer examined the commissive speech act inherent in the debate between President Barrack Obama and Mitt Romney in Second U.S. Presidential Debate edition. There are three problems in this study: (1a) what types of commisive speech act (1b) what are the classifications of commisive speech acts (2) what are the direct and indirect commisive speech act.This study used a qualitative approach. Research design was text analysis which was applied to analyze the data. The data were the sentences produced by Barack Obama and Mitt Romney in the Second U.S. Presidential Debate. The writer also put the results of the analysis in the table to make it easier to read the results of the analysis.The results showed there are kinds of commissive acts in the debate. Researchers found 23 conversations that indicate illocutionary acts of commissive. Of these 23, 2 were respectively offers, in which the President or governor speech aim to provide a quote form designs in revolution to the American nation. There were also 4 promises where the debater aimed to give a promise to perform his obligations as a good president for the country. After that, there are 6 refusings in which the speaker tried to give the refusal or denial of the statement that is not true. In addition, there are 6 vowing acts aimed to give oaths so that the listeners can be more confident and believe any major changes which are made to countries such as the U.S. increased the country's economy. Last is 5 volunteering acts which have a goal to not give immediate relief from the president who made volunteering acts without any specific purpose. All these results indicate that the debate contains move indirect sentences that have implied meaning and purposes.The writer suggests to the next reaserchers conduct a study on speech act focusing on two-way communication among other public figures because there will be more various types of illocutionary act in two-way communication.